2019
DOI: 10.3390/su11113179
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Demolition Waste in Romania: The Route from Illegal Dumping to Building Materials

Abstract: The paper performs a critical overview concerning the construction and demolition waste (C&DW) management issues in Romania. Five main stages related to C&DW management are highlighted such as: (i) illegal dumping on public lands; (ii) C&DW collection and disposal in urban landfills; (iii) C&DW treatment and reuse in civil constructions (roads, coating material for landfills); (iv) regional integrated waste management systems; (v) recycling of building materials (e.g., cement industry and recycled aggregates).… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 28 publications
0
34
0
1
Order By: Relevance
“…Corradini, Pierobon and Zanetti 2019The authors stated that the product environmental footprint (PEF) methodology allows the identification of the main hotspots and actions for reducing environmental impacts in existing buidings. Mihai (2019) The study revealed that poor monitoring of construction and demolition waste flows across Romanian counties and the geographical dimension of this waste stream collected by waste operators. Raouf and Al-Ghamdi (2019) The authors identified the main obstacles and limitations to BIM implementation in the green building industry.…”
Section: Constructionmentioning
confidence: 98%
“…Corradini, Pierobon and Zanetti 2019The authors stated that the product environmental footprint (PEF) methodology allows the identification of the main hotspots and actions for reducing environmental impacts in existing buidings. Mihai (2019) The study revealed that poor monitoring of construction and demolition waste flows across Romanian counties and the geographical dimension of this waste stream collected by waste operators. Raouf and Al-Ghamdi (2019) The authors identified the main obstacles and limitations to BIM implementation in the green building industry.…”
Section: Constructionmentioning
confidence: 98%
“…Illegal waste disposal has been identified as a major environmental degradation practices in the world (e.g. Mahayuddin et al, 2008;Mihai, 2019). In recent years, the increase in C & D waste in Tewodros, A., Abdulaziz, O and Haddush, G (MEJS) Mekelle city and subsequent improper handling has become a critical issue.…”
Section: Impact Of Construction Wastementioning
confidence: 99%
“…Mobile crushing plants could be an optimal solution for rural communities to deal with C&DW flows. This waste stream has a high potential for reuse, recovery, and recycling activities under circular economy prospects as new building materials for both urban and rural areas [51].…”
Section: Community Waste Management and Creative Reuse Of Waste Itemsmentioning
confidence: 99%